Design of Gating System for Green Sand Casting of Alumium Alloy - Mohamed Hashim, Muhammad Hishamuddin; Saleh, Aslinda (Progress in Engineering Application and Technology, 2021)
Sand casting is preferable and well-known as the most efficient way as it is cost efficient and can form shape through expendable mould process. The hollow cavity in the mould that determine the desired shape is then allowed to solidify. The implementation of gating system brought about the fundamental yields in the casting. Gating system design is very essential in the casting process and described as one of the key elements in determining good quality of casting. A gating system in charge of controlling the flow pattern and mould filling process throughout the casting process. Improper design of gating system would contribute into several casting defects during mould fillings and solidification phase, cause turbulence flow of molten metal and consequently damage the castings yielded. This study provides an in-depth analysis on the design of gating system for green sand casting of aluminium alloy. The main focus of this study was to propose the best gating system design with minimal casting defects, for instances, porosity, shrinkage and misrun. There were three different designs of gating system proposed in this study based on the previous researches with different parameters installed on each design of gating system. This study was designed in order to find out about the performances of various designs of gating system on the product of aluminium alloy castings in green sand casting process based on the previous researches. The variety of gating parameters were studied involving the type of feeding system, the shape of sprue, type of runner, number of gate as well as the functional value of sprue well on the molten aluminium alloy in green sand casting. Solidworks simulation analysis was implemented through the application of Solidworks software version 2019. The simulation analysis was applied on the design of gating system in examining the aspects of stress and displacement regarding the parts of the gating system design. The cost analysis was performed in this study through the quotation method in analyzing the estimation of the cost charged on the materials as well as the manufacturing costs involved in the fabrication of the gating system design. Gating system design II indicates very small amount of stress at the two ingates with yellow to orange colour of stress distribution ranging from 1.828e+08 N/m² to 2.031e+08 N/m² compared design I and III. The total cost for fabricating the best gating system design II is RM 699.40. As a conclusion, Solidwork analysis feature available in the software able to assist in the design selection for fabricating the matchplate pattern for green sand casting process.